Impact of Platinum on the Whole Mitochondrial Genome of Ovarian Carcinomas Both In Vivo and In Vitro. Issue 3 (1st March 2009) - Shi, Honghui; Pan, Lingya; Song, Tian
Abstract : Objectives: To investigate somatic mitochondrial DNA mutation in primary and recurrent ovarian carcinoma tissues as well as that in drug-resistant cell lines to illuminate the impact of chemotherapeutic drugs on mitochondrial DNA (mtDNA). Methods: Complete mtDNA genomes of 20 pairs of ovarian carcinomas and their matched normal tissues together with 2 ovarian carcinoma cell lines and their 4 platinum-resistant cell lines were sequenced. Mitochondrial DNA alterations, consequent amino acid alterations were compared between the 2 groups of patients and the 2 types of cell lines. Results: A large number of mtDNA new polymorphisms (55) and mutations (18) were identified in 20 ovarian carcinoma samples. Platinum-based chemotherapy did not increase the number of new polymorphisms ( P = 0.094), mutations ( P = 0.688), and consequent amino acid alterations ( P = 0.202 and 0.795). Data gained from the cell lines also indicated that platinum had some effect on the mitochondrial genome but not specific to particular positions. Conclusions: What we found suggested that mtDNA damage could be made by chemotherapeutic drugs but not as much as imagined in ovarian carcinomas. Some of the mtDNA defects might be part of the disease processes and cell properties as well as a consequence of treatment.